Salivary β2-microglobulin positively correlates with ESSPRI in patients with primary Sjögren's syndrome - Garza García, Felipe; Delgado García, Guillermo Rubén; Garza Elizondo, Mario Alberto; Ceceñas Falcón, Luis Ángel; Galarza Delgado, Dionicio Ángel; Riega Torres, Janett Carmen Luzmila (2017)
Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disorder largely distinguished by lymphocytic exocrinopathy.1 Salivary and lachrymal glands are mainly impaired in pSS. Saliva is therefore considered an optimal biological fluid that closely reflects the underlying autoimmune exocrinopathy.1,2 For instance, in those with